2017
DOI: 10.24875/ric.17002097
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characteristics of Exercise-Induced Bronchoconstriction in High School and College Athletes at 2,240 m Altitude

Abstract: AbstrACtbackground: athletes practicing strenuous physical activities may develop exercise-induced bronchoconstriction (eIB). We aimed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…Overall, we found that the prevalence of EIB was reported in a total of 35 of the 60 reviewed studies, using a combination of the methods listed above. The studies, main findings, and ratio of male and female enrolled subjects are summarized in Table 1 [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ]. Collectively, these studies enrolled 5103 athletes and reported a diagnosis of EIB in 1153 subjects.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, we found that the prevalence of EIB was reported in a total of 35 of the 60 reviewed studies, using a combination of the methods listed above. The studies, main findings, and ratio of male and female enrolled subjects are summarized in Table 1 [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ]. Collectively, these studies enrolled 5103 athletes and reported a diagnosis of EIB in 1153 subjects.…”
Section: Resultsmentioning
confidence: 99%
“…Aunque estas diferencias en resistencias en la altura, no se vieron con el método resistencia interrumpida (Rint), probablemente porque la IOS nos permite medir la fricción y resistencia del tejido elástico. Un estudio realizado en ciudad de México (2,240 msnm) en atletas, mostró una baja prevalencia de broncoespasmo inducido por ejercicio (EIB), postulando a la altura como un factor protector (11). Por último, la evaluación del intercambio gaseoso medido por la capacidad de difusión del monóxido de carbono por simple respiración (DICOsB) en niños y adolescentes de la ciudad de México, demostró unos valores más elevados que los que viven a nivel de mar (12).…”
Section: Sección Serie / Seriesunclassified